Kazys Pakštas: Culture and political stability - Pšibilskis, Vygintas Bronius (Politologija, 1999)
"Apostle of vitalism," "Lithuania’s most dynamic personality," "nation’s most distinguished moral leader," "generous fidget," "political idealist," "unrecognized harbinger," "Lithuanian Kasandra," "the great realist"—these were the epithets used to describe Kazys Pakštas, one of the most conspicuous scientists, enlighteners, publicists, and public men in the history of 20th-century Lithuania. In this article, the author, Vygintas Pšibilskis, unlocks the door to both the personal and scientific heritage of Kazys Pakštas, reveals together the original thoughts of this reflective thinker, and the ideas as have been put by other Lithuanian philosophers and public men with respect to both the works and the personal experience of this enlightener, who has left substantial signs in the history of Lithuania’s political thought. In some respects, in his works and thoughts, Kazys Pakštas resembles the ideas of the Huntingtons (Samuel Huntington and his father) together with other widely known geopoliticians (Ratzel, Haushofer), whose ideas he came to fit in the specific context of Lithuania. With a great number of journeys and trips, together with a long period of life he spent living abroad, in pocket, the scientist had come to adopt the western ideas of democracy and tolerance; he was among the very first who disseminated these ideas in Lithuania and stood ahead of those who set attempts to change the customs and traditions of political life. A sonorous voice of Pakštas reflected a deep understanding that they are the science and education together that should be the most powerful and essential forces upon which societal progress ought to count. By reason of this, he, on the one hand, tried actively to spread western dynamism in Lithuania, and on the other, sharply criticized the indifference of the national bureaucracy in relation to cultural problems. He believed that the main objective of every independent state is to create conditions for the survival of both the state and the nation and had in that sense named this objective as principal to cultural politics. Among other factors that predetermine the strength and resistibility of the state, K. Pakštas chose the number of inhabitants (anthropological or private economy), urban and rural capaciousness, intensity of the economy, exploitation of transit opportunities, moral and physical health of the nation, resolution of social problems, rational orchestration of emigration. Embracing a wide variety of factors and problems, in the Republic of Lithuania, he was among the first to express concisely what Lithuania’s national interests are—that is, the maintenance of the identity of state and the people (nation), precautionary measures against the external invasion and the ascendancy of big neighboring nations, preparation for a feasible loss of independence. In his reflections on the promotion of national and state resistibility, K. Pakštas came close to a modern understanding of power. On this basis, he devised the strategy of national security, based on the will of the nation to rely upon itself, upon the resources of their state, which depend upon the realization of intellectual potential, inter-relationship of political forces, level of democracy, good neighborly relationships with both large and small states, instead of confiding the fate of the nation to military measures. The heritage of Professor K. Pakštas is a valuable spring for Lithuania’s culturologists, politicians, and researchers in fields of political history and theory. Up-to-date, a number of problems ensued by the scientist remain as important as they were.